PEMBANGUNAN APLIKASI FORUM SEBAGAI SALAH SATU TOOLS KNOWLEDGE MANAGEMENT SYSTEM DENGAN PENDEKATAN INSTANT MESSAGING AND INTRANET FORUMS PADA PT ABI MAJU KONSULTAN DI PONTIANAK - Hasanudin Hasanudin (Universitas Bina Sarana Informatika, 2014)
Knowledge is a valuable asset for everyone no exception for the company. By Herbert (2007) Knowledge of a person can grow because of the experience, successes and failures and the learning process that meet all the time. Knowledge it self is divided into two parts that is